Arc flash analysis study in industry - Harna, Elavarasu (2010)
Nowadays, hazard that associated with arc flash incident is increasing every year by year. The increasing of the incident has been brought to our attention. This study proposed so that it can help the industries to eliminate or at least reduce those hazards. Through the analysis of this project, the limitation for the arc flash occurs will be proved through the stimulation of the short circuit calculation and the boundary calculation by using the ETAP software. There are few steps that will be included, which is data collection process, develop single line diagram, arcing short circuit calculations and also flash protection boundary calculations. The workers in industries should take the harm of arc flash as a serious matter and be aware of arc flash. The expected result from this project will be the limitation that will be gain in the end of this project. The limitations of the protective boundary to control the arc flash in industries. The limitations of the protective boundary from the result are also to control the usage of Personal Protective Equipment (PPE). For each distance form a system or work place there will be a certain suitable level of PPE. The result will help to reduce harm and accident that happens in industries. The analysis of this project basically will be based on industrial field, where the data that used to do the analysis will be involving the industry site